Labor regulations and European venture capital - Ant Bozkaya; William R. Kerr (Bank of Finland, 2013)
European nations substitute between employment protection regulations and labor market expenditures (e.g., unemployment insurance benefits) for providing worker insurance. Employment regulations more directly tax firms making frequent labor adjustments than other labor market insurance mechanisms. Venture capital investors are especially sensitive to these labor adjustment costs. Nations favoring labor market expenditures as the mechanism for providing worker insurance developed stronger venture capital markets over 1990-2008, especially in high volatility sectors. In this context, policy mechanisms are more important than the overall level of worker insurance.
URN:NBN:fi:bof-20140807409
Keywords: G24; J21; J65; L26; M13; O31; O32; O52; 330; employment protection regulations; dismissal costs; unemployment insurance benefits; private equity; venture capital; entrepreneurship